An Arabinogalactan from the Seeds of Limonia acidissima: Isolation, Purification and Structural Features - K. Mondal, Saroj; Ray, Bimalendu; Thakur, Swapnadip; K. Ghosal, Pradyot (Asian Journal of Chemistry, 2010)
Polysaccharides were extracted from the seeds of Limonia acidissima with water. The chemical compositions of the soluble extracts and insoluble materials were determined. Presence of pectic substances, polymers containing xylose and glucose and xylans were indicated. The material isolated by water was fractionated by anion exchange and gel permeation chromatography and the structure of the purified pectic polysaccharides was investigated using acid hydrolysis, methylation analysis, periodic oxidation and spectroscopic experiments. Type II arabinogalactan was the major polysaccharide in the water extract.